Iowa Birdline update, September 11-13, 1994 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1994)
Email of the Iowa Birdline update for September 11-13, 1994. Highlights of the update include the continued presence of a Long-tailed Jaeger and a Sabine's Gull in Sac County. Also of note were observations of a Red-necked Phalarope, a Western Grebe, and the continued presence of a Pacific Loon. Also included are handwritten notes for the next week's update with sightings of a Merlin, a Piping Plover, and a Cattle Egret. Epson - sheet feed/flatbed